The reaction to femicide in criminal law - Batrićević Ana (Temida, 2016)
Misogynous and sexist violence against women, which often results in death, represents a global problem. Numerous international and national legal instruments are dedicated to the prevention and sanctioning of violence against women. However, the reality implies that existing mechanisms of penal reaction to femicide, as its most extreme and brutal form, should be re-examined. Having in mind the frequency and severe consequences of this criminal offence and the discriminatory character of the message that the state sends by tolerating it or inadequately punishing its perpetrators, the author attempts to define femicide, to present basic forms of state reaction to femicide in comparative law as well as to analyze the features of femicide as an independent criminal offence. Arguing for the incrimination of femicide as an independent criminal offence, or as a special form of aggravated murder, the author points out that such solution could contribute to more precise observation of this form of crime, to a better estimation of the quality of the state‘ s reaction to it and to its more efficient suppression.